Comparative Heavy Metal Adsorption Using Magnetic, Carbon-Based, and Biopolymer Composite: A Critical Systematic Review - Sultan Napoleon; Mayang Fauziah Putri Kuntjahjono; Wikrama Sarweswara; Nugroho Adi Sasongko; Akhmad Rifa'i; Nuha Nuha; Rahmat Basuki (Indonesian Scholar Society, 2026)
The increasing contamination of aquatic environments by heavy metals has driven the continuous development of efficient, sustainable, and reusable adsorbent materials. This systematic review critically compares the adsorption performance of magnetic-, carbon-based-, and biopolymer-based composites used for heavy metal removal from aqueous solutions. The analysis integrates data from various studies published within the last decade, focusing on maximum adsorption capacity (qmax), specific surface area, magnetic properties, and adsorption isotherm models. Carbon-based adsorbents demonstrate high adsorption capacities (4.16–491 mg g⁻¹) due to their large surface areas and well-developed porosity, while biopolymer-based materials offer environmental sustainability and functional group diversity but generally exhibit lower adsorption performance unless modified with magnetic or carbon components. Magnetic adsorbents, particularly ferrite-based nanocomposites, exhibit exceptional adsorption capacities (up to 1951.98 mg g⁻¹ for Pb(II)) and high removal efficiencies exceeding 95%, with the added advantage of easy magnetic separation and recyclability. However, the long-term stability and regeneration efficiency of magnetic adsorbents remain critical challenges. The bibliometric analysis using VOSviewer further reveals that recent research trends are shifting from fundamental adsorption studies toward the development of multifunctional, hybrid composites that integrate magnetic, carbon, and biopolymer components. These advancements reflect a growing emphasis on enhancing adsorption efficiency, reusability, and environmental compatibility, providing a strong foundation for the design of next-generation adsorbents suitable for industrial-scale wastewater treatment.